Implementasi White Hat SEO (Search Engine Optimization) Pada Website E-Commerce Sayur Plagro.id - Indra Muliawan, I Gst Agung Ngurah; Wijaya ADH, IGKG Puritan; Desi Saryanti, I Gusti Ayu (UNIVERSITAS RAHARJA, 2023)
Internet users in Indonesia have increased by 64% of the total population in Indonesia in 2020. This number has increased by 17% compared to 2019. The website is one of the internet technologies that is not only a medium of information but also to support a company's business processes such as selling products and services online, but sales through the website cannot be done without the support of the right promotion strategy. Usually, 62% of internet users are interested in the first 10 or 20 pages of the SERP (Search Engine Result Page), and another 38% will look at the website on the next page. One method that can be used to get top rankings on search engines on the internet is to implement SEO methods. SEO (Search Engine Optimization) is a promotional technique that uses search engine optimization to ensure that a website ranks high or is on the first page on SERPs. One of the problems faced by the Plagro.id e-commerce website is the position in search engine search results based on the targeted keywords not being in an indexed position on the SERP (Search Engine Results Page) or ranked 100 and above on the SERP (Search Engine Results) Page), so that it is not visible or is still on a page far from the SERP. This study implemented one of the SEO methods, namely White Hat SEO on the Plagro.id e-commerce website, then tested using Serprobot Tools. After the website is optimized, it is tested again with the same testing tools. From the results of this study, the results of increasing the ranking of the Plagro.id e-commerce website in the SERP after implementing SEO.